PERAN BRAND TRUST MEMEDIASI PENGARUH E-WOM TERHADAP KEPUTUSAN PEMBELIAN SCARLETT WHITENING DI KOTA DENPASAR - dewi, ni ketut fayola cahya; Ketut Giantar, I Gusti Ayu (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2025)
This study aims to analyze the role of brand trust in mediating the influence of e-wom on purchasing decisions. This study was conducted on Scarlett Whitening consumers in Denpasar City with a quantitative approach using the associative causality method. The sample determination used a non-probability sampling method with a purposive sampling technique and a sample of 100 samples was used and used a survey method with offline and online questionnaires. The theory used is the S-O-R Theory and AISAS Theory. The data analysis technique in this study is path analysis using SPSS. The results of this study state that all hypotheses are accepted. E-wom has a positive and significant influence on purchasing decisions. E-wom has a positive and significant influence on brand trust. Brand trust has a positive and significant influence on purchasing decisions. Brand trust is able to partially mediate the influence of e-wom on purchasing decisions of Scarlett Whitening consumers in Denpasar City. The results of this study provide empirical evidence that brand trust has an important role in e-wom on purchasing decisions. The implication of this study is the importance of Scarlett Whitening building consumer trust in the brand by providing relevant information to build positive e-wom which is expected to increase consumer purchasing decisions of Scarlett Whitening in Denpasar City.